Systemic inflammatory Th1 cytokines during Trypanosoma cruzi infection disrupt the typical anatomical cell distribution and phenotypic/functional characteristics of various cell subsets within the thymus - Viano, María Estefanía (2024)
The thymus plays a crucial role in T cell differentiation, a complex process influenced by various factors such as antigens, the microenvironment and thymic architecture. The way the thymus resolves infections is critical, as chronic persistence of microbes or inflammatory mediators can obstruct the differentiation. Here, we illustrate that following inflammatory T helper 1 infectious processes like those caused by Candida albicans or Trypanosoma cruzi, single positive thymocytes adopt a mature phenotype. Further investigations focused on T. cruzi infection, reveal a substantial existence of CD44+ cells in both the cortical and medullary areas of the thymus at the onset of infection. This disturbance coincides with heightened interferon gamma (IFNγ) production by thymocytes and an increased cytotoxic capacity against T. cruzi-infected macrophages. Additionally, we observe a reduced exportation capacity in T. cruzi-infected mice. Some alterations can be reversed in IFNγ knockout mice (KO). Notably, the majority of these effects can be replicated by systemic expression of interleukin (IL)-12+IL-18, underlining the predominantly inflammatory rather than pathogen-specific nature of these phenomena. Understanding the mechanisms through which systemic inflammation disrupts normal T cell development, as well as subsequent T cell exportation to secondary lymphoid organs (SLO) is pivotal for comprehending susceptibility to diseases in different pathological scenarios.